Batik di Era Teknologi Digital - Djanjang Purwo Sedjati (Ars: Jurnal Seni Rupa dan Desain, 2011)
Batik in the Era of  Digital Technology. The process of  Batik making (handmade batik and printed batik) operates certain techniques and equipments that are certainly influenced by the technology development. The effects do not only touch the production process but also the distribution process. Digital technology is also applied in this field that in one way or another promotes the batik art. Digital technology is already used in creating batik design. It results in various type of  design, for example the fractal batik that makes over the geometrical forms. Digital technology applied in designing batik causes a more effective and efficient making process. This technology completes the manual process that is still employed until today.Keywords: batik, digital, fractal, art, craft